ANALYSIS COMPARATIVE OF ISLAMIC BANKING HEALTH LEVELS IN ASIA USING RGEC METHOD - Wijaya, Ahmad Mada; Wardana, Guntur Kusuma (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2024)
This research aims to compare the health levels of Sharia banks in Asia over the period 2017-2022 using the RGEC method, considering the factors of Risk Profile, Good Corporate Governance, Earnings, and Capital. Financial ratios used to assess bank health include risk profile using 2 ratios namely NPF and FDR, GCG factor using selfassessment, Earnings using 4 ratios namely ROA, ROE, BOPO, and capital factors including the CAR ratio. The type of research used is quantitative descriptive research. The data obtained are secondary data in the form of annual financial reports of the companies. The research results show significant differences in the health of Sharia banks in Asia measured using the RGEC method. Sharia Banks categorized as